"Blackness is not just a single definition": multimodal composition as an exercise for surfacing and scaffolding student theorizing in a Black Studies classroom. Issue 2 (12th July 2021) - Ohito, Esther O.
Abstract : Purpose: This study aims to investigate multimodal composition as an exercise or tool for teaching students theory building. To illustrate, an analysis of artifacts comprising a student's multimodal composition, which was created in response to a multipart literacy assignment on theorizing Blackness, is analyzed. Design/methodology/approach: Afrocentricity served as both theoretical moor and research methodology. Qualitative case study, focusing on the case of an individual student, was the research method used. Findings: Multimodal composition was an effective exercise for surfacing the multidimensionality of a student's complex knowledge while simultaneously placing the student in the powerful position of theorist. The process of composing multimodally integrated reading, writing and speaking skills while revealing the focal student's need for targeted writing intervention. Practical implications: The study evidences multimodal composition as a useful exercise for capturing students' nuanced interpretations or students' critical theorizing as well as meaningfully incorporating and assessing students' literacy skills. Originality/value: Exposure to preexisting theory alone relegates students to the realm of passive knowledge consumers. This undermines the emancipatory and justice-oriented objectives of critical education, which ideally contributes to social change by challenging dominant power structures and distorted perspectives of marginalized persons. To be empowered agentic learners, students need to be both taught how to theorize and engaged as theorists. This study shows how multimodal composition can be used as a liberatory literacy tool for those intertwined pedagogical purposes.